High-temperature-resistant adhesive tape for lithium battery and preparation method of high-temperature-resistant adhesive tape

Through the combination of modified butyl rubber, polyisobutylene and modified silicone, the problem of low mechanical strength and insufficient flame resistance of lithium battery high-temperature tape at high temperatures is solved, and higher tensile strength and resistance are achieved Thermal aging and flame retardant properties improve the overall performance of lithium battery tape.

CN119193015AInactive Publication Date: 2024-12-27NANJING ZHANYI TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411561404.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium battery high-temperature resistant tapes have decreased mechanical strength in high-temperature environments, and the material becomes brittle after thermal aging, and the flame resistance is insufficient.

Method used

Using modified butyl rubber, polyisobutene, modified silicone, modified vermiculite powder, modified calcium carbonate and other materials, the interaction between modified silicone and butyl rubber, the elastomer characteristics of polyisobutene and modified The filler effect of vermiculite powder and modified calcium carbonate forms high-strength and flame retardant tape.

Benefits of technology

It improves the tensile strength, heat-resistant aging performance and flame retardant properties of the tape, delays the thermal decomposition and aging process, and enhances the stability and safety at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193015A_ABST
    Figure CN119193015A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant adhesive tape for a lithium battery and a preparation method of the high-temperature-resistant adhesive tape, belongs to the technical field of adhesive tape processing, and is used for solving the technical problem that the mechanical strength, high-temperature aging resistance and flame resistance of a high-temperature-resistant adhesive tape for a lithium battery in the prior art need to be further improved. The adhesive tape comprises a base tape layer, an adhesive layer and release paper, wherein one side of the base tape layer is coated with the adhesive layer; the release paper is adhered to the adhesive layer; the base tape layer comprises the following components in parts by weight: 20-30 parts of modified butyl rubber, 30-50 parts of polyisobutene, 7-9 parts of modified siloxane, 3-5 parts of an additive and 35-45 parts of mixed filler; according to the invention, polysiloxane modified nitrile rubber, polyisobutene and modified siloxane are reinforced by a mixed filler composed of modified vermiculite powder and modified calcium carbonate, so that the high-temperature aging resistance of the high-temperature-resistant adhesive tape is effectively improved, and the tensile property and flame resistance grade of the high-temperature-resistant adhesive tape are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesive tape processing, and in particular to a high temperature resistant adhesive tape for lithium batteries and a preparation method thereof. Background Art

[0002] With the continuous development of science and technology, lithium batteries are used more and more widely in various fields, especially in electric vehicles, mobile devices and energy storage systems. With the development of high-current fast charging technology, lithium batteries will release a lot of heat during the charging and discharging process. The high-temperature resistant tape for lithium batteries is to meet the working needs of lithium batteries in high temperature environments. This tape can not only protect the lithium battery from working normally at high temperatures, but also effectively prevent the leakage of electrolyte inside the battery and the intrusion of external heat sources, so as to improve the safety and reliability of lithium batteries.

[0003] Prior art, a Chinese patent with publication number CN114539940A, discloses a method for preparing a high temperature resistant adhesive tape for lithium batteries, wherein polyester and silicone oil are weighed and heated to 185-200°C, mixed for 0.8-2.5h to obtain a mixture A, PMDA, hexagonal boron nitride, polyethylene glycol and isopropanol are weighed, vibrated for 12-18min, heated to 50-65°C, diaminodiphenyl ether is added, vibrated for 8-15min, heated to 75-85°C, reacted at a constant temperature for 1.5-3.5h, and distilled to obtain a mixture B, which is added to the mixture A in 3-5 batches, heated to 205-220°C, reacted for 2-3h, and a substrate is obtained by film formation, the substrate is activated by an activation solution, and then an adhesive is coated on the substrate, dried, and rolled to obtain a high temperature resistant adhesive tape to ensure good temperature resistance, insulation performance and thermal conductivity.

[0004] However, the thermal conductivity of the tape in the prior art is relatively high. The temperature of the tape rises rapidly in a high temperature environment, which makes it easy to undergo thermal aging. Especially in a hot and humid environment, the tape becomes brittle after thermal aging, and its mechanical strength decreases accordingly. In addition, the tape on the market often uses an organic polymer as a matrix, which is flammable itself. Especially after experiencing thermal aging, the flame retardancy of the material will further decrease. The flame retardancy of the tape needs to be further improved.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a high temperature resistant tape for lithium batteries and a preparation method thereof, so as to solve the technical problem that the mechanical strength, high temperature aging resistance and flame retardancy of the high temperature resistant tape for lithium batteries in the prior art need to be further improved.

[0007] The object of the present invention can be achieved by the following technical solution: A high temperature resistant adhesive tape for lithium batteries, comprising a base tape layer, an adhesive layer coated on one side of the base tape layer, and a release paper adhered to the adhesive layer;

[0008] The base belt layer comprises the following components in parts by weight: 20-30 parts of modified butyl rubber, 30-50 parts of polyisobutylene, 7-9 parts of modified siloxane, 3-5 parts of additives and 35-45 parts of mixed fillers;

[0009] The mixed filler consists of modified vermiculite powder and modified calcium carbonate in a weight ratio of 7:2-3.

[0010] Furthermore, the additives are composed of a vulcanizer, a vulcanization accelerator, a softener, a dispersant, a lubricant, and an antioxidant in a weight ratio of 3:1:2:4:3:5, the vulcanizer is sulfur, the vulcanization accelerator is accelerator TMTD, the softener is phthalate, the dispersant is stearate, the lubricant is one or two of liquid paraffin and microcrystalline paraffin, and the antioxidant is one or more of antioxidant D, antioxidant RD, and antioxidant MB.

[0011] Further, the modified butyl rubber is processed by the following steps:

[0012] A1. Add 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane, allyldimethoxysilane and anhydrous ethanol into a reaction kettle and stir. The temperature of the reaction kettle is raised to 55-65° C., and sodium hydroxide solution is added into the reaction kettle. The reaction is kept warm for 4-6 hours, and modified polysiloxane is obtained by post-treatment.

[0013] The synthetic reaction formula of modified polysiloxane is:

[0014]

[0015] The synthetic reaction mechanism of modified polysiloxane is:

[0016] Under alkaline conditions, siloxane bonds of 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane and allyldimethoxysilane are hydrolyzed into silanol groups, and the generated silanol groups undergo condensation reactions to form siloxy bonds, thereby preparing modified polysiloxanes having a polysiloxane skeleton structure modified with olefin double bonds.

[0017] A2. Add butyl rubber and xylene into a high-pressure reactor and stir until the system is dissolved. Add modified polysiloxane and initiator into the high-pressure reactor. Stably increase the temperature of the high-pressure reactor to 120-130° C., keep the temperature for reaction for 3-4 hours, and obtain modified butyl rubber by post-treatment.

[0018] The synthetic reaction mechanism of modified butyl rubber is:

[0019] Under the action of the initiator, the olefin double bonds on the modified polysiloxane react with the butyl rubber molecular chain to undergo free radical polymerization to form a modified butyl rubber having polysiloxane chain segments reinforcing the butyl rubber.

[0020] Further, in step A1, the molar ratio of the 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane to allyldimethoxysilane is 10:1, the amount ratio of the 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane, anhydrous ethanol and sodium hydroxide solution is 1g:10mL:1mL, the concentration of the sodium hydroxide solution is 0.3-0.5mol / L, and the post-treatment comprises: after the reaction is completed, the solvent is evaporated under reduced pressure, the temperature of the reactor is lowered to room temperature, and the reactor is heated to room temperature. Purified water and dichloromethane are added, stirred at room temperature for 10-15 minutes, and the mixture is allowed to stand for separation. The organic phase is washed twice with purified water and then transferred to a rotary evaporator with a water bath temperature of 45-55° C., and the solvent is evaporated under reduced pressure to obtain a modified polysiloxane. In step A2, the amount ratio of the butyl rubber, xylene, modified polysiloxane and initiator is 3g:10mL:1g:0.04g, and the initiator is dibenzoyl peroxide. The post-treatment includes: after the reaction is completed, the solvent is evaporated under reduced pressure to obtain a modified butyl rubber.

[0021] Furthermore, it is characterized in that the preparation method of the modified siloxane is: octavinyl octasilsesquioxane, DOP, toluene and an initiator are added to a nitrogen-protected reactor and stirred, the temperature of the reactor is increased to 80-90° C., the reaction is kept warm for 6-8 hours, and the modified siloxane is obtained by post-treatment.

[0022] The synthetic reaction formula of modified siloxane is:

[0023]

[0024] Where:

[0025] The synthetic reaction mechanism of modified siloxane is:

[0026] The initiator decomposes under heating conditions to generate free radicals, so that the olefin double bond on the octavinyl octasilsesquioxane reacts with the hydrogen on the DOP molecule to form a DOP molecule modification on the octavinyl octasilsesquioxane molecule to prepare a modified siloxane.

[0027] Furthermore, the amount ratio of the octavinyl octasilsesquioxane to DOP is 1 mol:8.5 mol, the amount ratio of the octavinyl octasilsesquioxane, toluene and initiator is 1 g:10 mL:0.02 g, the initiator is azobisisobutyronitrile, and the post-treatment includes: after the reaction is completed, toluene is evaporated under reduced pressure, the temperature of the reactor is lowered to room temperature, dichloromethane is added to the reactor, and the reaction mixture is stirred and kept warm until the system is dissolved, ethyl acetate is added dropwise to the reactor, and after the addition is completed, the reaction mixture is stirred and kept warm for 30-50 minutes, and the reaction mixture is filtered, the filter cake is washed twice with ethyl acetate and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain modified siloxane.

[0028] Further, the modified vermiculite powder is processed by the following steps:

[0029] B1, adding expanded vermiculite powder and hydrochloric acid solution into a reactor and stirring, raising the temperature of the reactor to 70-80°C, keeping the temperature and stirring for 2-3h, and post-treating to obtain activated vermiculite powder;

[0030] B2. Add hexadecyltrimethylammonium bromide and deionized water into a reactor and stir until the system is dissolved. Then add activated vermiculite into the reactor. Raise the temperature of the reactor to 60-70°C, keep warm and stir for 2-3h, and obtain modified vermiculite powder by post-treatment.

[0031] The synthetic reaction mechanism of modified vermiculite powder is:

[0032] Under acidic conditions, the exchangeable cations on the surface of expanded vermiculite powder exchange with the hydrogen ions in the hydrochloric acid solution, opening the interlayer structure of the vermiculite powder, increasing its specific surface area and porosity, thereby improving its adsorption capacity and reaction activity. Hexadecyltrimethylammonium bromide is a cationic surfactant whose long-chain alkyl group has hydrophobic properties, while the ammonium bromide part has hydrophilic properties. Hexadecyltrimethylammonium bromide is adsorbed on the surface and interlayer of activated vermiculite through electrostatic action, forming an intercalation effect, and the modified vermiculite powder is prepared.

[0033] Furthermore, in step B1, the particle size of the expanded vermiculite powder is 70-80 μm, the amount ratio of the expanded vermiculite powder to the hydrochloric acid solution is 1 g: 10 mL, the concentration of the hydrochloric acid solution is 0.03-0.05 mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed 3 times with purified water and then dried, the filter cake is transferred to a drying oven at a temperature of 80-90° C., and vacuum dried to constant weight to obtain activated vermiculite powder; in step B2, the amount ratio of the hexadecyltrimethylammonium bromide, deionized water and activated vermiculite is 1 g: 10 mL: 3 g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed 3 times with deionized water and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80° C., and vacuum dried to constant weight to obtain modified vermiculite powder.

[0034] Furthermore, the preparation method of modified calcium carbonate is: adding nano calcium carbonate and deionized water into a reactor and stirring, raising the temperature of the reactor to 45-55°C, stirring for 30-50 minutes, adding sodium alginate solution into the reactor, keeping warm and stirring for 2-3 hours, and post-treating to obtain modified calcium carbonate.

[0035] The synthetic reaction mechanism of modified calcium carbonate is:

[0036] By stirring the solution, the sodium alginate molecules are fully in contact with and interact with the nano-calcium carbonate particles. The carboxyl groups in the sodium alginate molecules interact with the calcium ions on the surface of the nano-calcium carbonate. The sodium alginate is adsorbed on the surface of the nano-calcium carbonate particles by electrostatic action to form a coating layer, thereby preparing modified calcium carbonate.

[0037] Furthermore, the dosage ratio of the nano calcium carbonate, deionized water and sodium alginate solution is 1g:40mL:30mL, the sodium alginate solution is composed of sodium alginate and deionized water in a dosage ratio of 1g:60mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with anhydrous ethanol for 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 45-55°C, and vacuum dried to constant weight to obtain modified calcium carbonate.

[0038] The present invention also provides a method for preparing a high temperature resistant adhesive tape for a lithium battery, comprising the following steps:

[0039] S1, adding modified butyl rubber, polyisobutylene, modified siloxane and additives into an internal mixer at a temperature of 85-95° C. and blending for 10-15 minutes, adding mixed fillers into the internal mixer in batches, and after the addition is completed, continuing to blend for 30-40 minutes to obtain a mixed rubber material;

[0040] S2, adding the mixed rubber material into a calender, calendering to prepare a long thin sheet with a thickness of 0.15±0.01 mm, cutting and splicing to obtain a base strip blank;

[0041] S3, placing the base tape blank into a flat vulcanizer at a temperature of 80-90°C, and vulcanizing at this temperature for 3-5 minutes to obtain the base tape;

[0042] S4, press the silicone rubber glue to 130-150g / m 2 The coating amount is evenly coated on one side of the base tape to form an adhesive layer on the base tape, and a release paper is attached to the top of the adhesive layer, and the film is air-dried and rolled up to obtain a high temperature resistant tape.

[0043] The present invention has the following beneficial effects:

[0044] 1. The high temperature resistant adhesive tape for lithium batteries of the present invention is modified by introducing modified polysiloxane to modify butyl rubber. The molecular chains of the modified polysiloxane interact with the molecular chains of the butyl rubber to form new chemical bonds, which can strengthen the connection between the molecular chains of the butyl rubber, so that when the overall material is stretched by an external force, the molecular chains are not easy to slip and break, thereby improving the tensile strength. In addition, the butyl rubber itself also has good thermal stability, and the combination with the modified polysiloxane further improves the heat aging resistance. As an elastomer, the molecular chain of polyisobutylene has high flexibility and can undergo large deformation under the action of external force without being easy to break, so that the polyisobutylene and the modified butyl rubber cooperate with each other to form a good entanglement effect, thereby improving the tensile properties of the overall material of the adhesive tape.

[0045] 2. The high temperature resistant adhesive tape for lithium batteries of the present invention contains a plurality of silicon oxygen bonds and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in the modified siloxane molecule, which improves its compatibility with the modified nitrile rubber, and the phosphorus element in the modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide participates in the free radical reaction in the combustion process, consumes the free radicals in the combustion chain, and thus reduces the combustion speed, and the silicon element in the adhesive tape material can form a dense carbonized layer at high temperature, and this carbonized layer can isolate oxygen and combustible gases, and cooperates with DOP to further improve the flame retardant properties of the material, and the mixed filler is in the flame retardant direction, and the modified vermiculite powder can release crystal water at high temperature, and this water can absorb heat and reduce the temperature of the combustion area, and the modified calcium carbonate can decompose at high temperature to produce non-combustible gases such as water and carbon dioxide, dilute the oxygen concentration in the combustion area, thereby inhibiting the combustion reaction and reducing the combustion performance of the material.

[0046] 3. The high temperature resistant adhesive tape for lithium batteries of the present invention increases the number of active groups and porosity of the surface of vermiculite powder by activating the vermiculite powder, so that hexadecyltrimethylammonium bromide can form an intercalation effect in the vermiculite powder. The modified calcium carbonate is coated with sodium alginate to improve the surface properties of the modified vermiculite powder and the modified calcium carbonate, and enhance the interface bonding force between the modified vermiculite powder and the modified calcium carbonate and the matrix. The strong interface bonding force enables the filler to transfer stress more effectively during the stretching process, reduces stress concentration and the generation of cracks, thereby improving the tensile strength of the high temperature resistant adhesive tape. The modified vermiculite powder The introduction of modified calcium carbonate limits the movement of the molecular chains of the matrix material to a certain extent. The modified vermiculite powder itself has certain toughness and elasticity, and can absorb part of the energy during the stretching process, hindering the crack propagation during the stretching process, so that the tape can withstand greater deformation before breaking. Modified vermiculite powder and modified calcium carbonate, as inorganic fillers, have high thermal stability and can maintain structural stability at high temperatures, thereby slowing down the thermal decomposition and aging process of the matrix material. In addition, the modified vermiculite powder can also serve as a thermal barrier to block the transfer of heat, reduce the temperature of the matrix material, and further improve the heat aging resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0048] Figure 1 The infrared spectrum analysis diagram of expanded vermiculite powder and modified vermiculite powder in the present invention;

[0049] Figure 2 : is the infrared spectrum analysis diagram of octavinyl octasilsesquioxane and modified siloxane in the present invention;

[0050] Figure 3 The infrared spectrum analysis diagram of the nano calcium carbonate and modified calcium carbonate in the present invention. DETAILED DESCRIPTION

[0051] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] The silicone rubber glue in the present invention is selected from Taizhou Yizhan Electronic Technology Co., Ltd., and the model is YZ-820 silicone primer;

[0053] Polyisobutylene was selected from Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd. The product name is polyisobutylene PB2400, and the viscosity (100°C, cst) is 4500-4900 cst.

[0054] Example 1

[0055] This embodiment provides a method for preparing a high temperature resistant adhesive tape for a lithium battery, comprising the following steps:

[0056] S1. Preparation of modified butyl rubber

[0057] Weigh: 222.4 g of 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane, 13.2 g of allyldimethoxysilane and 2224 mL of anhydrous ethanol, add them to a reactor and stir, raise the temperature of the reactor to 55°C, add 222.4 mL of 0.3 mol / L sodium hydroxide solution to the reactor, keep the reaction for 4 hours, evaporate the solvent under reduced pressure, lower the temperature of the reactor to room temperature, add 1000 mL of purified water and 2000 mL of dichloromethane to the reactor, stir at room temperature for 10 minutes, stand and separate, wash the organic phase twice with purified water, transfer it to a rotary evaporator with a water bath temperature of 45°C, evaporate the solvent under reduced pressure to obtain a modified polysiloxane;

[0058] Weigh: 300 g of butyl rubber and 1000 mL of xylene are added to a high-pressure reactor and stirred until the system is dissolved. 100 g of modified polysiloxane and 4 g of dibenzoyl peroxide are added to the high-pressure reactor. The temperature of the high-pressure reactor is stably increased to 120° C. and the reaction is kept warm for 3 hours. The solvent is evaporated under reduced pressure to obtain modified butyl rubber.

[0059] S2. Preparation of modified siloxane

[0060] Weigh: 63.3 g of octavinyl octasilsesquioxane, 183.7 g of DOP, 633 mL of toluene and 1.3 g of azobisisobutyronitrile, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 80°C, keep the reaction for 6 hours, evaporate toluene under reduced pressure, lower the temperature of the reactor to room temperature, add 600 mL of dichloromethane to the reactor, keep the reaction temperature and stir until the system is dissolved, add 1000 mL of ethyl acetate dropwise to the reactor, keep the reaction temperature and stir for 30 minutes after the addition is complete, filter, wash the filter cake twice with ethyl acetate and then drain, transfer the filter cake to a drying oven at 60°C, and vacuum dry to constant weight to obtain modified siloxane.

[0061] S3. Preparation of modified vermiculite powder

[0062] Add expanded vermiculite powder with a particle size of 70-80 μm and 0.03 mol / L hydrochloric acid solution in a dosage ratio of 1 g: 10 mL into a reactor and stir, raise the temperature of the reactor to 70° C., keep stirring for 2 hours, lower the temperature of the reactor to room temperature, filter by suction, wash the filter cake with purified water for 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 80° C., and vacuum dry to constant weight to obtain activated vermiculite powder;

[0063] Weigh: 100 g of hexadecyltrimethylammonium bromide and 1000 mL of deionized water are added to a reactor and stirred until the system is dissolved, then 300 g of activated vermiculite is added to the reactor, the temperature of the reactor is raised to 60°C, and the mixture is kept warm and stirred for 2 hours. The temperature of the reactor is lowered to room temperature, and the filter cake is filtered off. The filter cake is washed three times with deionized water and then dried. The filter cake is transferred to a drying oven at a temperature of 70°C and vacuum dried to constant weight to obtain modified vermiculite powder.

[0064] S4. Preparation of modified calcium carbonate

[0065] Sodium alginate and deionized water were added into a reaction kettle at a ratio of 1 g:60 mL and stirred until the system was dissolved to obtain a sodium alginate solution;

[0066] Weigh: 50 g of nano calcium carbonate and 2000 mL of deionized water, add them into a reactor and stir, raise the temperature of the reactor to 45°C, stir for 30 min, add 1500 mL of sodium alginate solution into the reactor, keep warm and stir for 2 h, lower the temperature of the reactor to room temperature, filter, wash the filter cake with anhydrous ethanol 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 45°C, and vacuum dry it to constant weight to obtain modified calcium carbonate.

[0067] S5. Preparation of mixed rubber

[0068] The modified vermiculite powder and the modified calcium carbonate are uniformly mixed in a weight ratio of 7:2 to obtain a mixed filler;

[0069] The sulfur, the vulcanization accelerator TMTD, the dibutyl phthalate, the sodium stearate, the liquid paraffin, and the antioxidant D are uniformly mixed in a weight ratio of 3:1:2:4:3:5 to obtain an additive;

[0070] Weigh by weight: 20 parts of modified butyl rubber, 30 parts of polyisobutylene, 7 parts of modified siloxane and 3 parts of additives, add to an internal mixer at a temperature of 85°C and blend for 10 minutes. Add 35 parts of mixed filler to the internal mixer in batches. After the addition is completed, continue blending for 30 minutes to obtain a mixed rubber material.

[0071] S6. Prepare baseband

[0072] The mixed rubber material is added into a calender, and calendered into a long sheet with a thickness of 0.15±0.01 mm, and then cut and spliced ​​to obtain a base tape blank;

[0073] The base tape blank was placed in a flat-plate vulcanizer at 80°C and vulcanized for 3 minutes to obtain the base tape.

[0074] S7. Preparation of high temperature resistant tape

[0075] Press the silicone rubber glue to 130g / m 2 The coating amount is evenly coated on one side of the base tape to form an adhesive layer on the base tape, and a release paper is attached to the top of the adhesive layer, and the film is air-dried and rolled up to obtain a high temperature resistant tape.

[0076] Example 2

[0077] This embodiment provides a method for preparing a high temperature resistant adhesive tape for a lithium battery, comprising the following steps:

[0078] S1. Preparation of modified butyl rubber

[0079] Weigh: 222.4 g of 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane, 13.2 g of allyldimethoxysilane and 2224 mL of anhydrous ethanol, add them to a reactor and stir, raise the temperature of the reactor to 60°C, add 222.4 mL of 0.4 mol / L sodium hydroxide solution to the reactor, keep the reaction for 5 hours, evaporate the solvent under reduced pressure, lower the temperature of the reactor to room temperature, add 1000 mL of purified water and 2000 mL of dichloromethane to the reactor, stir at room temperature for 13 minutes, stand and separate, wash the organic phase twice with purified water, transfer it to a rotary evaporator with a water bath temperature of 50°C, evaporate the solvent under reduced pressure to obtain a modified polysiloxane;

[0080] Weigh: 300 g of butyl rubber and 1000 mL of xylene are added to a high-pressure reactor and stirred until the system is dissolved. 100 g of modified polysiloxane and 4 g of dibenzoyl peroxide are added to the high-pressure reactor. The temperature of the high-pressure reactor is steadily increased to 125° C. and the reaction is kept warm for 3.5 hours. The solvent is evaporated under reduced pressure to obtain modified butyl rubber.

[0081] S2. Preparation of modified siloxane

[0082] Weigh: 63.3 g of octavinyl octasilsesquioxane, 183.7 g of DOP, 633 mL of toluene and 1.3 g of azobisisobutyronitrile, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 85°C, keep the reaction warm for 7 hours, evaporate toluene under reduced pressure, lower the temperature of the reactor to room temperature, add 600 mL of dichloromethane to the reactor, keep the reaction warm and stir until the system is dissolved, add 1000 mL of ethyl acetate dropwise to the reactor, keep the reaction warm and stir for 40 minutes after the addition is complete, filter with suction, wash the filter cake twice with ethyl acetate and then drain, transfer the filter cake to a drying oven at 65°C, and vacuum dry to constant weight to obtain modified siloxane.

[0083] S3. Preparation of modified vermiculite powder

[0084] Add expanded vermiculite powder with a particle size of 70-80 μm and 0.04 mol / L hydrochloric acid solution in a dosage ratio of 1 g:10 mL into a reactor and stir, raise the temperature of the reactor to 75°C, keep stirring for 2.5 hours, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water for 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 85°C, and vacuum dry to constant weight to obtain activated vermiculite powder;

[0085] Weigh: 100 g of hexadecyltrimethylammonium bromide and 1000 mL of deionized water are added to a reactor and stirred until the system is dissolved. Then 300 g of activated vermiculite is added to the reactor, the temperature of the reactor is raised to 65°C, and the mixture is kept warm and stirred for 2.5 hours. The temperature of the reactor is lowered to room temperature, and the filter cake is filtered off. The filter cake is washed three times with deionized water and then dried. The filter cake is transferred to a drying oven at a temperature of 75°C and vacuum dried to constant weight to obtain modified vermiculite powder.

[0086] S4. Preparation of modified calcium carbonate

[0087] Sodium alginate and deionized water were added into a reaction kettle at a ratio of 1 g:60 mL and stirred until the system was dissolved to obtain a sodium alginate solution;

[0088] Weigh: 50 g of nano calcium carbonate and 2000 mL of deionized water are added to a reactor and stirred. The temperature of the reactor is raised to 50°C and stirred for 40 min. 1500 mL of sodium alginate solution is added to the reactor and stirred for 2.5 h. The temperature of the reactor is lowered to room temperature and filtered. The filter cake is washed three times with anhydrous ethanol and then dried. The filter cake is transferred to a drying oven at a temperature of 50°C and vacuum dried to constant weight to obtain modified calcium carbonate.

[0089] S5. Preparation of mixed rubber

[0090] The modified vermiculite powder and the modified calcium carbonate are uniformly mixed in a weight ratio of 7:2.5 to obtain a mixed filler;

[0091] The sulfur, the vulcanization accelerator TMTD, the dioctyl phthalate, the calcium stearate, the microcrystalline wax and the antioxidant RD are uniformly mixed in a weight ratio of 3:1:2:4:3:5 to obtain an additive;

[0092] Weigh by weight: 25 parts of modified butyl rubber, 40 parts of polyisobutylene, 8 parts of modified siloxane and 5 parts of additives, add them to an internal mixer at a temperature of 90°C and blend for 13 minutes. Add 40 parts of mixed filler to the internal mixer in batches. After the addition is completed, continue blending for 35 minutes to obtain a mixed rubber material.

[0093] S6. Prepare baseband

[0094] The mixed rubber material is added into a calender, and calendered into a long sheet with a thickness of 0.15±0.01 mm, and then cut and spliced ​​to obtain a base tape blank;

[0095] The base tape blank was placed in a flat-plate vulcanizer at 85°C and vulcanized for 4 minutes to obtain the base tape.

[0096] S7. Preparation of high temperature resistant tape

[0097] Press the silicone rubber glue to 140g / m 2 The coating amount is evenly coated on one side of the base tape to form an adhesive layer on the base tape, and a release paper is attached to the top of the adhesive layer, and the film is air-dried and rolled up to obtain a high temperature resistant tape.

[0098] Example 3

[0099] This embodiment provides a method for preparing a high temperature resistant adhesive tape for a lithium battery, comprising the following steps:

[0100] S1. Preparation of modified butyl rubber

[0101] Weigh: 222.4 g of 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane, 13.2 g of allyldimethoxysilane and 2224 mL of anhydrous ethanol, add them to a reactor and stir, raise the temperature of the reactor to 65°C, add 222.4 mL of 0.5 mol / L sodium hydroxide solution to the reactor, keep the reaction for 6 hours, evaporate the solvent under reduced pressure, lower the temperature of the reactor to room temperature, add 1000 mL of purified water and 2000 mL of dichloromethane to the reactor, stir at room temperature for 15 minutes, stand and separate, wash the organic phase twice with purified water, transfer it to a rotary evaporator with a water bath temperature of 55°C, evaporate the solvent under reduced pressure to obtain a modified polysiloxane;

[0102] Weigh: 300 g of butyl rubber and 1000 mL of xylene are added to a high-pressure reactor and stirred until the system is dissolved. 100 g of modified polysiloxane and 4 g of dibenzoyl peroxide are added to the high-pressure reactor. The temperature of the high-pressure reactor is stably increased to 130° C. and the reaction is kept warm for 4 hours. The solvent is evaporated under reduced pressure to obtain modified butyl rubber.

[0103] S2. Preparation of modified siloxane

[0104] Weigh: 63.3 g of octavinyl octasilsesquioxane, 183.7 g of DOP, 633 mL of toluene and 1.3 g of azobisisobutyronitrile, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 90°C, keep the reaction warm for 8 hours, evaporate toluene under reduced pressure, lower the temperature of the reactor to room temperature, add 600 mL of dichloromethane to the reactor, keep the reaction warm and stir until the system is dissolved, add 1000 mL of ethyl acetate dropwise to the reactor, keep the reaction warm and stir for 50 minutes after the addition is complete, filter, wash the filter cake twice with ethyl acetate and then drain, transfer the filter cake to a drying oven at 70°C, and vacuum dry to constant weight to obtain modified siloxane.

[0105] S3. Preparation of modified vermiculite powder

[0106] Add expanded vermiculite powder with a particle size of 70-80 μm and 0.05 mol / L hydrochloric acid solution in a dosage ratio of 1 g: 10 mL into a reactor and stir, raise the temperature of the reactor to 80° C., keep stirring for 3 hours, lower the temperature of the reactor to room temperature, filter by suction, wash the filter cake with purified water for 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 90° C., and vacuum dry to constant weight to obtain activated vermiculite powder;

[0107] Weigh: 100 g of hexadecyltrimethylammonium bromide and 1000 mL of deionized water are added to a reactor and stirred until the system is dissolved, then 300 g of activated vermiculite is added to the reactor, the temperature of the reactor is raised to 70°C, and the mixture is kept warm and stirred for 3 hours. The temperature of the reactor is lowered to room temperature, and the filter cake is filtered off. The filter cake is washed three times with deionized water and then dried. The filter cake is transferred to a drying oven at 80°C and vacuum dried to constant weight to obtain modified vermiculite powder.

[0108] S4. Preparation of modified calcium carbonate

[0109] Sodium alginate and deionized water were added into a reaction kettle at a ratio of 1 g:60 mL and stirred until the system was dissolved to obtain a sodium alginate solution;

[0110] Weigh: 50 g of nano calcium carbonate and 2000 mL of deionized water are added to a reactor and stirred. The temperature of the reactor is raised to 55°C and stirred for 50 min. 1500 mL of sodium alginate solution is added to the reactor and stirred for 3 h. The temperature of the reactor is lowered to room temperature and filtered. The filter cake is washed three times with anhydrous ethanol and then dried. The filter cake is transferred to a drying oven at a temperature of 55°C and vacuum dried to constant weight to obtain modified calcium carbonate.

[0111] S5. Preparation of mixed rubber

[0112] The modified vermiculite powder and the modified calcium carbonate are uniformly mixed in a weight ratio of 7:3 to obtain a mixed filler;

[0113] The sulfur, the vulcanization accelerator TMTD, the diethyl phthalate, the zinc stearate, the liquid paraffin, and the antioxidant MB are uniformly mixed in a weight ratio of 3:1:2:4:3:5 to obtain an additive;

[0114] Weigh by weight: 30 parts of modified butyl rubber, 50 parts of polyisobutylene, 9 parts of modified siloxane and 5 parts of additives, add them to an internal mixer at a temperature of 95°C and blend for 15 minutes. Add 45 parts of mixed filler to the internal mixer in batches. After the addition is completed, continue blending for 40 minutes to obtain a mixed rubber material.

[0115] S6. Prepare baseband

[0116] The mixed rubber material is added into a calender, and calendered into a long sheet with a thickness of 0.15±0.01 mm, and then cut and spliced ​​to obtain a base tape blank;

[0117] The base tape blank was placed in a flat-plate vulcanizer at a temperature of 90°C and vulcanized for 5 minutes to obtain the base tape.

[0118] S7. Preparation of high temperature resistant tape

[0119] Press the silicone rubber glue to 150g / m 2 The coating amount is evenly coated on one side of the base tape to form an adhesive layer on the base tape, and a release paper is attached to the top of the adhesive layer, and the film is air-dried and rolled up to obtain a high temperature resistant tape.

[0120] Comparative Example 1

[0121] The difference between this comparative example and Example 3 is that step S1 is eliminated, and the modified butyl rubber in step S5 is replaced by the butyl rubber in step S1.

[0122] Comparative Example 2

[0123] The difference between this comparative example and Example 3 is that step S3 is eliminated, and the modified vermiculite powder in step S5 is replaced by the expanded vermiculite powder in step S3.

[0124] Comparative Example 3

[0125] The difference between this comparative example and Example 3 is that step S4 is eliminated, and the modified calcium carbonate in step S5 is replaced by the nano calcium carbonate in step S4.

[0126] Comparative Example 4

[0127] The difference between this comparative example and Example 3 is that no modified calcium carbonate is added to the mixed filler in step S5.

[0128] Performance Test:

[0129] The tensile strength and elongation at break of the high temperature resistant tape samples prepared in Examples 1-3 and Comparative Examples 1-4 were tested with reference to the standard GB / T 30776-2014 "Test method for tensile strength and elongation at break of adhesive tapes";

[0130] The flame retardancy grades of the high temperature resistant tape samples prepared in Examples 1-3 and Comparative Examples 1-4 were tested with reference to the standard GB / T 15903-1995 "Test method for flame retardancy of pressure-sensitive adhesive tapes - hanging method";

[0131] The high temperature resistant tape samples prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to heat aging according to the standard GB / T 32368-2015 “Test method for high temperature and high humidity aging of adhesive tapes”, and the tensile strength and elongation at break of the samples were measured. The specific test results are shown in Table 1 below.

[0132] Table 1-Performance test data of the sample

[0133]

[0134]

[0135] Data Analysis:

[0136] A comparative analysis of the data in Table 1 above shows that the tensile strength of the high temperature resistant tape prepared by the present invention reaches 68.2 MPa, and the elongation at break reaches 980%. After high temperature and high humidity aging treatment, the tensile strength reaches 65.0 MPa, the retention reaches 95.3%, the elongation at break reaches 920%, the retention reaches 93.9%, and the flame retardant grade reaches 0. All performance parameters are better than those of the comparative example, indicating that the present invention enhances the polysiloxane-modified nitrile rubber, polyisobutylene and modified siloxane by using a mixed filler composed of modified vermiculite powder and modified calcium carbonate, which not only effectively improves the high temperature aging resistance of the high temperature resistant tape, but also improves its tensile properties and flame retardant grade.

[0137] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high temperature resistant tape for lithium batteries, characterized in that: It includes a base tape layer, an adhesive layer coated on one side of the base tape layer, and a release paper adhered to the adhesive layer; The base belt layer comprises the following components in parts by weight: 20-30 parts of modified butyl rubber, 30-50 parts of polyisobutylene, 7-9 parts of modified siloxane, 3-5 parts of additives and 35-45 parts of mixed fillers; The mixed filler consists of modified vermiculite powder and modified calcium carbonate in a weight ratio of 7:2-3.

2. A high temperature resistant adhesive tape for lithium batteries according to claim 1, characterized in that: Modified butyl rubber is processed by the following steps: A1. Add 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane, allyldimethoxysilane and anhydrous ethanol into a reaction kettle and stir. The temperature of the reaction kettle is raised to 55-65° C., and sodium hydroxide solution is added into the reaction kettle. The reaction is kept warm for 4-6 hours, and modified polysiloxane is obtained by post-treatment. A2. Add butyl rubber and xylene into a high-pressure reactor and stir until the system is dissolved. Add modified polysiloxane and initiator into the high-pressure reactor. Stably increase the temperature of the high-pressure reactor to 120-130° C., keep the temperature for reaction for 3-4 hours, and obtain modified butyl rubber by post-treatment.

3. A high temperature resistant adhesive tape for lithium batteries according to claim 2, characterized in that: In step A1, the molar ratio of the 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane and allyldimethoxysilane is 10:1, the amount ratio of the 1,3-diethoxy-1,1,3,3-tetramethyldisiloxane, anhydrous ethanol and sodium hydroxide solution is 1g:10mL:1mL, and the concentration of the sodium hydroxide solution is 0.3-0.5mol / L; in step A2, the amount ratio of the butyl rubber, xylene, modified polysiloxane and initiator is 3g:10mL:1g:0.04g, and the initiator is dibenzoyl peroxide.

4. The high temperature resistant adhesive tape for lithium battery according to claim 1, characterized in that: The preparation method of modified siloxane is as follows: octavinyl octasilsesquioxane, DOP, toluene and initiator are added into a nitrogen-protected reactor and stirred, the temperature of the reactor is increased to 80-90° C., the reaction is kept warm for 6-8 hours, and the modified siloxane is obtained by post-treatment.

5. A high temperature resistant adhesive tape for lithium batteries according to claim 4, characterized in that: The usage ratio of the octavinyl octasilsesquioxane and DOP is 1 mol: 8.5 mol, the usage ratio of octavinyloctasilsesquioxane, toluene and initiator is 1 g:10 mL:0.02 g, and the initiator is azobisisobutyronitrile.

6. The high temperature resistant adhesive tape for lithium battery according to claim 1, characterized in that: Modified vermiculite powder is processed by the following steps: B1, adding expanded vermiculite powder and hydrochloric acid solution into a reactor and stirring, raising the temperature of the reactor to 70-80°C, keeping the temperature and stirring for 2-3h, and post-treating to obtain activated vermiculite powder; B2. Add hexadecyltrimethylammonium bromide and deionized water into a reactor and stir until the system is dissolved. Then add activated vermiculite into the reactor. Raise the temperature of the reactor to 60-70°C, keep warm and stir for 2-3h, and obtain modified vermiculite powder by post-treatment.

7. A high temperature resistant adhesive tape for lithium batteries according to claim 6, characterized in that: In step B1, the particle size of the expanded vermiculite powder is 70-80 μm, the usage ratio of the expanded vermiculite powder and the hydrochloric acid solution is 1 g:10 mL, and the concentration of the hydrochloric acid solution is 0.03-0.05 mol / L; in step B2, the usage ratio of hexadecyltrimethylammonium bromide, deionized water and activated vermiculite is 1 g:10 mL:3 g.

8. The high temperature resistant adhesive tape for lithium battery according to claim 1, characterized in that: The preparation method of modified calcium carbonate is as follows: adding nano calcium carbonate and deionized water into a reactor and stirring, raising the temperature of the reactor to 45-55° C., stirring for 30-50 minutes, adding sodium alginate solution into the reactor, keeping warm and stirring for 2-3 hours, and post-treating to obtain modified calcium carbonate.

9. A high temperature resistant adhesive tape for lithium batteries according to claim 8, characterized in that: The dosage ratio of the nano calcium carbonate, deionized water and sodium alginate solution is 1g:40mL:30mL, and the sodium alginate solution is composed of sodium alginate and deionized water in a dosage ratio of 1g:60mL.

10. A method for preparing a high temperature resistant adhesive tape for lithium batteries according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, adding modified butyl rubber, polyisobutylene, modified siloxane and additives into an internal mixer at a temperature of 85-95° C. and blending for 10-15 minutes, adding mixed fillers into the internal mixer in batches, and after the addition is completed, continuing to blend for 30-40 minutes to obtain a mixed rubber material; S2, adding the mixed rubber material into a calender, calendering to prepare a long thin sheet with a thickness of 0.15±0.01 mm, cutting and splicing to obtain a base strip blank; S3, placing the base tape blank into a flat vulcanizer at a temperature of 80-90°C, and vulcanizing at this temperature for 3-5 minutes to obtain the base tape; S4, press the silicone rubber glue to 130-150g / m 2 The coating amount is evenly coated on one side of the base tape to form an adhesive layer on the base tape, and a release paper is attached to the top of the adhesive layer, and the film is air-dried and rolled up to obtain a high temperature resistant tape.